Semantic Web : concepts, technologies and applications - Breitman, Karin. ((NASA monographs in systems and software engineering), 2007)
This book provides a well-paced introduction to the semantic Web, which is gaining in understanding and acceptance as new applications are realized in industry, academic, and government environments. It provides a succinct account of this new Web, its concepts, technologies and applications, and in particular demonstrates how semantic Web technologies may be integrated and realised in several application domains including: software agents, semantic desktops, fine arts, and geospatial applications. The book is intended as a reference text on the semantic Web for software engineers, database and information technology students, academics and practitioners. It differs from other available books on the topic because, rather than presenting the semantic Web as a quilt of disconnected topics, it provides a comprehensible body of concepts and related technologies. The book reflects the authors’ experience in research, graduate teaching, corporate training, industry and government projects grounded on the semantic Web. The future of the Internet -- Concepts -- Ontology in computer science -- Knowledge representation in description logic -- RDF and RDF schema -- OWL -- Rule languages -- Semantic Web services -- Technologies -- Methods for ontology development -- Ontology sources -- Semantic Web software tools -- Applications -- Software agents -- Semantic desktop -- Ontology applications in art -- Geospatial semantic Web.